RNA-sequencing and behavioral testing reveals inherited physical inactivity co-selects for anxiogenic behavior without altering depressive-like behavior in Wistar rats. (14th May 2021) - Kelty, Taylor J.; Brown, Jacob D.; Kerr, Nathan R.; Roberts, Michael D.; Childs, Tom E.; Cabrera, Omar H.; Manzella, Francesca M.; Miller, Dennis K.; Taylor, George T.; Booth, Frank W.
Highlights: Selective breeding rats for low voluntary running (LVR) distance co-selected for anxiogenic behavior, without altering depressive-like behavior in LVR rats. RNA-sequencing and immunoblotting revealed transcriptional and protein networks associated with downregulated nervous system development and function in LVR rats. Combined, behavioral and molecular data revealed physical inactivity as an additional vulnerability to the etiology of anxiety and identified potential therapeutic targets for anxiety. Abstract: Physical inactivity is positively associated with anxiety and depression. Considering physical inactivity, anxiety, and depression each have a genetic basis for inheritance, our lab used artificial selectively bred low-voluntary running (LVR) and wild type (WT) female Wistar rats to test if physical inactivity genes selected over multiple generations would lead to an anxiety or depressive-like phenotype. We performed next generation RNA sequencing and immunoblotting on the dentate gyrus to reveal key biological functions from heritable physical inactivity. LVR rats did not display depressive-like behavior. However, LVR rats did display anxiogenic behavior with gene networks associated with reduced neuronal development, proliferation, and function compared to WT counterparts. Additionally, immunoblotting revealed LVR deficits in neuronal development and function. To our knowledge, this is the first study to show that by selectively breeding for physical inactivity genes, anxiety-like genes were co-selected. The study also reveals molecular insights to the genetic influences that physical inactivity has on anxiety-like behavior.